Islam and Christianity mutual perceptions since the mid-20th century - Waardenburg, Jean Jacques (Peeters, 1998)
The importance of studying past and present relationships between Islam and Christianity as well as between Muslims and Christians of different persuasions has now become generally recognized. The present volume of scholarly studies focusses on changes which have occurred in these relationships during the last forty years. The papers examine new Catholic, Protestant and Orthodox views of Islam and a broad variety of views of Christianity held by Muslims from India, Iran, North Africa, and the Near East, including some "fundamentalist" authors in Egypt and Lebanon. The book contains a moving testimony from a Muslim intellectual in Sarajevo written during the siege of the city. Nearly all contributions were discussed at the Cret Berard (Switzerland) symposium in April 1995.